The Impact of Climate Change on Hurricane Damages in the United States - Mendelsohn, Robert; Emanuel, Kerry; Chonabayashi, Shun (2012)
This paper quantifies hurricane damage caused by climate change across the US. A damage function is estimated from historic hurricane data to measure the impacts at each location given the storm's strength. The minimum barometric pressure of each storm turns out to be a better indicator of damages than the traditional measure of maximum wind speed. A hurricane generator in the Atlantic Ocean is then used to create 5000 storms with and without climate change. Combining the location and intensity of each storm with the income and population projected for each location, it is possible to estimate a detailed picture of how hurricanes will impact each state with and without climate change. Income and population growth alone increase expected baseline damage from $9 to $27 billion per year by 2100. Climate change is expected to increase damage by another $40 billion. Over 85 percent of these impacts are in Florida and the Gulf states. The 10 percent most damaging storms cause 93 percent of expected damage.